Selected traditional Chinese medicine interventions for post-stroke cerebral edema: a review integrating clinical evidence and mechanistic insights - Huang, Junyue; Jin, Yujia; Chen, Yuping; Wang, Mengsi; Wu, Jian (Frontiers in Pharmacology, 2025)
BackgroundStroke is a leading cause of global death and disability. Post-stroke cerebral edema significantly worsens neurological outcomes. While conventional therapies face safety limitations, selected traditional Chinese medicine (TCM) interventions offer a potential alternative.Aim of the studyThis narrative review aims to comprehensively evaluate the efficacy and safety of TCM interventions for post-stroke cerebral edema and elucidate their potential mechanisms based on experimental evidence.Materials and methodsA systematic literature search was conducted in PubMed, Web of Science, and other databases using keywords related to stroke, cerebral edema, and TCM interventions. Studies were screened according to predefined inclusion criteria to ensure methodological rigor.ResultsClinical and preclinical studies indicate that TCM interventions can reduce cerebral edema volume, improve neurological outcomes, and exhibit good safety. These effects may be associated with modulation of ion homeostasis and aquaporins, neuroinflammatory inhibition, blood-brain barrier protection, oxidative stress reduction, and apoptosis suppression.ConclusionSelected TCM interventions show promise for post-stroke cerebral edema. Their clinical experience and mechanistic insights provide a valuable foundation for future research and drug development.